Operational risk allocation in urban rail transit public–private partnership projects - Xiang, Pengcheng; Zhang, Qianman; Jiang, Qiuyan; Liu, Zhaowen (Frontiers in Environmental Science, 2022)
Operation risk (OR) has affected sustainable development of urban rail transit (URT), public-private partnership (PPP) projects in China. Balanced distribution of operational risks among stakeholders (the public, government, and private companies) involved in URT PPP projects can maximize overall profit. Quantitative analysis of operational risk allocation of urban rail transit PPP project is the key to achieve balance. Few existing studies have quantitatively analyzed operation risk allocation (ORA) in URT PPP project. The objective of this research is to construct a quantitative risk allocation model among three participants by using cooperative game theory. The risk allocation model was modified based on the consideration of four factors affecting the allocation of operational risks: controllability, risk loss, affordability, and handling cost. A case was used as an empirical example and possible problems were illustrated. The result show it is necessary and feasible to let the public bear part of the operational risk of the project by raising ticket prices. The results reveal that the public will play an important role in balancing risk allocation. This study shows that an ORA model can suggest how to make the risk allocation process more reasonable, fair, and stable. Meanwhile, the quantitative approach proposed can also be used by stakeholders in achieving fairness and stability of the partnership.